Urban planning research from 2014-2024: a systematic literature review using text mining techniques - Carpentieri, Gerardo; Ascione, Laura (TeMA - Journal of Land Use, Mobility and Environment, 2025)
Urban planning is a crucial aspect of city development as it addresses issues such as mobility, environmental concerns, and urban design. The discipline of urban planning has evolved to meet the needs and challenges of urban areas. Recent research on urban planning has focused on understanding the field’s interdisciplinary nature, thus integrating aspects of design, policy, law, social sciences, and engineering. The importance of data and digitisation in urban planning as well as urban planning’s crucial role in achieving sustainable cities have also been recognised. The current study examines the evolution of urban planning research through a systematic review of the literature (SRL) published between 2014 and 2024, with text-mining techniques being employed for this endeavour. The present SRL is an analysis of a corpus of 65,368 scientific articles published in Scopus. The inclusion of the term ’urban planning’ in the title of the article is a fundamental criterion. In addition, a categorisation of words into three primary subgroups was conducted, based on the predominant themes that underpin scientific study and research activities. The subgroups were designated as follows: Research topics, Methods and techniques and Spatial dimensions and place. The results indicate that there is a growing emphasis on interdisciplinary approaches, complex and data-rich information integration. During the observation period, some of these approaches became more stable and significant, particularly for the words included in the Methods and Techniques and Spatial Dimensions and Places groups. For instance, the progressive affirmation of words is closely associated with the implementation of solutions involving spatial information systems and the importance of urban planning in achieving sustainable cities.